PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL, KOMPETENSI SUMBER DAYA MANUSIA DAN PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH KABUPATEN GIANYAR - Putu Cita Ayu; Ni Putu Ayu Kusumawati (UNHI Press, 2020)
This study aims to determine the effect of the application of accrual-based government accounting standards, human resource competencies and internal control on the quality of financial statements of the Gianyar Regency government. The type of data used in this study is a type of quantitative data while the data sources used in this study are primary and secondary data sources. The population used in this study was 36 departments in the Gianyar Regency Regional Organizations Organization. The sample in this study used a purposive sampling method, with a sample of 91 respondents working in the finance department. Data was collected using the questionnaire method. The data analysis technique used in this study is multiple linear regression analysis. The results showed that the application of accrual-based government accounting standards, human resource competence and internal control had a positive effect on the quality of local government financial reports in Gianyar Regency. This shows that the higher the application of accrual-based government accounting standards, human resource competencies and internal control, the higher the quality of local government financial reports in Gianyar Regency.